The given differential equation is
"\\frac{d^2y}{dx^2}+\\frac{dy}{dx}-2y=-6 \\ sin2x-18 \\ cos2x" .
The auxiliary equation is "m^2+m-2=0"
"\\implies m^2+2m-m-2=0"
"\\implies m(m+2)-1(m+2)=0"
"\\implies (m+2)(m-1)=0"
"\\implies m=1,-2"
"\\therefore C.F.=A\\ e^x+B\\ e^{-2x}"
Now , "P.I.=\\frac{1}{D^2+D-2}(-6\\ sin2x-18\\ cos2x)"
"=\\frac{1}{D^2+D-2}(-6\\ sin2x)+\\frac{1}{D^2+D-2}(-18\\ cos2x)"
"= \\frac{-6}{-4+D-2}(sin2x)+\\frac{-18}{-4+D-2}(cos2x)"
"=\\frac{-6}{D-6}(sin2x)-\\frac{18}{D-6}(cos2x)"
"=-6\u00d7\\frac{D+6}{D^2-36}(sin2x)-18\u00d7\\frac{D+6}{D^2-36}(cos2x)"
"=\\frac{6}{40}\u00d7(2\\ cos2x+6\\ sin2x)+\\frac{18}{40}\u00d7(-2\\ sin2x +6\\ cos2x)"
"=(\\frac{18}{20}+\\frac{-18}{20})sin2x+(\\frac{6}{20}+\\frac{54}{20})cos2x"
"=3 \\ cos2x" .
Therefore the complete solution is
"y=A\\ e^x+B \\ e^{-2x}+3\\ cos2x" ...................(1)
Differentiating (1) ,we get
"y'=A\\ e^x-2B\\ e^{-2x}-6\\ sin2x" .............(2)
But given that "y(0)=2" and "y'(0)=2" .
Therefore from equation (1) and (2) ,we get
"A+B+3=2 \\ ,\\implies A+B=-1" .............(3)
"A-2B=2" .........(4)
Subtracting (4) from (3) ,we get
"3B=-3 \\ , \\implies B=-1"
Putting the value of B in equation (3) ,we get
A=0.
"\\therefore y=-e^{-2x}+3 \\ cos2x"
Comments
Leave a comment